2018
DOI: 10.1111/gec3.12402
|View full text |Cite
|
Sign up to set email alerts
|

Geohumanities and climate change skepticism

Abstract: The voices of the climate “skeptics” or “deniers” are an unavoidable component of the current politics of climate change. Geographers have engaged with the politics of climate science, the dissemination of scientific knowledge, and how the dominant discourse of climate science frames the debate as apolitical, but they have not directed much attention to climate skeptic literature itself. I suggest that despite this lacunae, geographers have developed the necessary tools to understand climate skeptic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Riley E Dunlap & Jacques, 2013;Jacques, Dunlap, & Freeman, 2008;Schlosser, 2018;Workman et al, 2018). The skepticism has been mainly linked to US climate change politics (R E Dunlap & McCright, 2011;Riley E Dunlap & Jacques, 2013;Workman et al, 2018).…”
Section: Identities and Vested Interestsmentioning
confidence: 99%
“…Riley E Dunlap & Jacques, 2013;Jacques, Dunlap, & Freeman, 2008;Schlosser, 2018;Workman et al, 2018). The skepticism has been mainly linked to US climate change politics (R E Dunlap & McCright, 2011;Riley E Dunlap & Jacques, 2013;Workman et al, 2018).…”
Section: Identities and Vested Interestsmentioning
confidence: 99%
“…They cover a specter of related phenomena from repression of the problem in everyday life to organized, politically and economically motivated skepticism (e.g. Dunlap & McCright 2011, Nordgaard 2011, Schlosser 2018. This research has also shown how active skeptics often emphasize the uncertainty of climate change research and some actors are even manufacturing data to underscore the uncertainty (Dunlap & McCright 2010).…”
Section: Undermining the Exemplarity Of The Hurricanementioning
confidence: 99%
“…Several scholars have argued that climate change skepticism is often related to an embracement of industrial modernity (e.g. Anshelm & Hultman 2015: 100-119, Dunlap & McCright 2011, Schlosser 2018. This might also be the case with these texts, at least they repudiate any attempt to understand the present as a crisis of modernity.…”
Section: Culture Unboundmentioning
confidence: 99%
“…Debates over the ontological significance, theoretical implications, and practical challenges of “living in the Anthropocene” (Kress & Stine, ) have enlivened scholarship in geography and allied social sciences (for reviews, see Castree, ; Castree, ; Castree, ; Cook, Rickards, & Rutherfurd, ; Dalby, ; Lorimer, ; Schlosser, ; Swanson, Bubandt, & Tsing, ). Determining a date when humans irrevocably became a geological force demands and promises a union between social and physical sciences (Ellis, Maslin, Boivin, & Bauer, ).…”
Section: Introductionmentioning
confidence: 99%